2013
DOI: 10.6061/clinics/2013(05)17
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of serum albumin levels on the recurrence of stage I non-small cell lung cancer

Abstract: OBJECTIVE:Patients with stage I non-small cell lung cancer who have undergone complete surgical resection harbor a 30% risk for tumor recurrence. Thus, the identification of factors that are predictive for tumor recurrence is urgently needed. The aim of this study was to test the prognostic value of serum albumin levels on tumor recurrence in patients with stage I non-small cell lung cancer.METHODS:Stage I non-small cell lung cancer patients who underwent complete surgical resection of the primary tumor at Zhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 37 publications
1
51
0
3
Order By: Relevance
“…An elevated pretreatment PLR has been shown to predict poor outcome in the setting of SRS for early-stage NSCLC. Furthermore, hypoalbuminemia has been validated to serve as a marker for systemic inflammation (11), and is found to predict disease recurrence after complete resection of early-stage NSCLC (9,10). Therefore, although novel in the setting of brain SRS, our finding that markers of systemic inflammation prior to SRS predict poor outcome is supported by these previous data in different treatment settings.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…An elevated pretreatment PLR has been shown to predict poor outcome in the setting of SRS for early-stage NSCLC. Furthermore, hypoalbuminemia has been validated to serve as a marker for systemic inflammation (11), and is found to predict disease recurrence after complete resection of early-stage NSCLC (9,10). Therefore, although novel in the setting of brain SRS, our finding that markers of systemic inflammation prior to SRS predict poor outcome is supported by these previous data in different treatment settings.…”
Section: Discussionsupporting
confidence: 81%
“…Pre-treatment markers of systemic inflammation, including an elevated platelet-to-lymphocyte ratio (PLR), elevated neutrophil count, low lymphocyte count and low serum albumin concentration, have been found to predict responses to anti-neoplastic therapies and disease outcomes across multiple different malignancies (5)(6)(7)(8)(9)(10)(11). However, these markers and the role the systemic immune system plays in treatment outcomes in the setting of SRS for brain metastases have yet to be fully evaluated.…”
mentioning
confidence: 99%
“…6,9,27,28 It has also been shown that pretreatment lymphocytopenia predicts for poor antitumor responses in lung cancer patients receiving chemotherapy. 13 Although we do not know why we did not find these pretreatment immune parameters to predict for disease control in the setting of SBRT, this finding might potentially be related to the unique mechanisms of SBRT.…”
Section: Discussionmentioning
confidence: 98%
“…Up to now, hypoalbuminemia has been reported as an independent negative prognostic factor for survival in several cancers including lung (Gupta et al, 2010), gastric (Onate-Ocana et al, 2007), colorectal and breast (Gupta et al, 2010). Also low serum albumin level was shown to be an important prognostic factor for tumor recurrence and correlate with poor survival in NSCLC patients (Jin et al, 2013;Yildirim et al, 2013). Similar to these results, in our study, we observed that patients with decreased albumins had poor survival compared to those with high albumin in patients with lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 98%